Slim for life [compact disc, unabridged] : my insider secrets to simple, fast, and lasting weight loss - Michaels, Jillian (Random House Audio, 2013)
Outlines a plan for rapid and permanent weight loss, identifying gimmick-free practices for enabling positive health transformations.